Building Student Skills: Putting Process First in Assessment in Elementary Schools (IJORER : International Journal of Recent Educational Research, 2026)
Objective: In modern education, assessment is often considered a tool to measure student learning outcomes. However, this approach often ignores the processes students go through to achieve these outcomes. This study aims to explore the impact of implementing process-based assessment in sixth-grade learning, specifically on enhancing students' abilities in communication, teamwork, and critical analysis. The approach taken in this research is a qualitative descriptive technique approach, involving data collection through observation, interviews, and document analysis. The results show that the implementation of process-based assessment significantly increased students' active participation, which was reflected in their confidence when expressing ideas and contributing in groups. This study highlights an innovative shift towards process-oriented assessment, advocating for an educational paradigm that recognizes students' individual needs and promotes meaningful learning experiences. Recommendations for educators include designing inclusive assessment strategies and providing constructive feedback to foster important skills in early childhood students, ultimately improving educational outcomes in elementary schools.